Changes in the Splenic Melanomacrophage Centre Surface Area in Southern Bluefin Tuna (Thunnus maccoyii) Are Associated with Blood Fluke Infections - Nowak, Barbara F. (Pathogens, 2021)
Melanomacrophage centres (MMCs) are aggregates of macrophages accumulating various pigments. They have been proposed as an indicator of fish immune response. Blood flukes are common parasites in farmed fish. Two cohorts of wild Southern Bluefin Tuna (Thunnus maccoyi) were examined at transfer, before treatment against blood flukes (pre-treatment) and at harvest. MMCs were assessed in histological sections using image analysis, while Cardicola forsteri and Cardicola orientalis infection severity was determined using qPCR, count of adult flukes in heart flushes and count of eggs in gill filaments. Fish from both cohorts showed the same pattern in the changes in the surface area of MMCs. The surface area of splenic MMCs increased over the ranching duration and was positively correlated to the PCR determined copy numbers of Cardicola forsteri ITS2 rDNA in the gills of those fish. However, the infection with blood fluke was more variable, both between cohorts and individuals within the same cohort. Eggs of blood fluke were detected in renal MMCs using histology. Cardicola forsteri had a higher prevalence than Cardicola orientalis. This study contributes to our understanding of blood fluke infections in Southern Bluefin Tuna and their interactions with MMCs.